KIRI ISLAM HASSAN HANAFI DAN RELEVANSINYA DENGAN PERISTIWA PENINDASAN MUSLIM UGHIUR CHINA TAHUN 2019 - Rohmatun Nafi'ah (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2020)
This article discusses about Hasan Hanafi's Islamic Left Concept and its relevance to Muslim oppression in Uighur China. The Hasan Hanafi's Islamic Left Conceptarethe idea of a campaign of fight colonialism, retardation, and campaign of strive for independence, justice, and unite Muslims in one unit, al Jami’ah al-Islamiyyah or al- Jamiah Al- Syarqiyah. The Hasan Hanafi's Islamic Left Concept are interesting to study its relevance to Muslim oppression in Uighur China. In China there are regulations that prohibit the spread of Uighur Muslims. This article use qualitative and descriptive-analytical approaches with library data source. The finding of this article is thatthe relevance of Hasan Hanafi's Islamic Left to the events of China's Uighur Muslim oppression lies in the second pillar of the concept of Islamic Left, that is the urgency of challenging Western civilizationby re-actualizing Islamic thought using liberation theology.